Abuse Potential of Buprenorphine/Samidorphan Combination Compared to Buprenorphine and Placebo: A Phase 1 Randomized Controlled Trial. (13th August 2018) - Pathak, Sanjeev; Vince, Bradley; Kelsh, Debra; Shram, Megan J.; Setnik, Beatrice; Lu, Hong; Nangia, Narinder; Stanford, Arielle D.; Ehrich, Elliot
Abstract: Buprenorphine/samidorphan combination (BUP/SAM) is an opioid system modulator being investigated as adjunctive treatment for major depressive disorder. BUP/SAM is a fixed‐dose combination of buprenorphine, a partial μ‐opioid receptor agonist and κ‐opioid receptor antagonist, and samidorphan, a μ‐opioid receptor antagonist added to address the abuse and dependence potential of buprenorphine. In this study, we assessed the effect of samidorphan on the abuse potential of buprenorphine in the BUP/SAM combination in nondependent, recreational, adult opioid users (ClinicalTrials.gov ID: NCT02413281). Participants were randomized to 6 treatments in a blinded, Williams crossover design: placebo, BUP/SAM at the intended therapeutic dose (2 mg/2 mg), at 4‐fold (8 mg/8 mg) and 8‐fold (16 mg/16 mg) the therapeutic dose, and buprenorphine alone (8 mg and 16 mg). The primary end point was maximum effect (Emax ) on the visual analog scale for "at the moment" Drug Liking. Emax of Drug Liking for the BUP/SAM 2 mg/2 mg dose was similar to that for placebo (median within‐subject difference [90% confidence interval]: 2.5 [0.0–9.0]). The supratherapeutic doses of BUP/SAM showed differences of small magnitude on Drug Liking Emax compared to placebo. Drug Liking Emax for all BUP/SAM doses were significantly lower than those observed for either buprenorphine dose alone. Fewer participants reported adverse events associated with abuse potential with BUP/SAM than with buprenorphine alone, and the overall safety profile of BUP/SAM was consistent with prior reports in healthy volunteers. These findings indicate that samidorphan substantially reduces the abuse potential of buprenorphine in the BUP/SAM combination.